2014
DOI: 10.1021/es503869k
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Arsenite Methyltransferase from an Archaeon,Methanosarcina acetivoransC2A

Abstract: Arsenic is a ubiquitous toxic contaminant in the environment. The methylation of arsenic can affect its toxicity and is primarily mediated by biological processes. Few studies have focused on the mechanism of arsenic methylation in archaea although archaea are widespread in the environment. Here, an arsenite [As(III)] methyltransferase (ArsM) was identified and characterized from an archaeon Methanosarcina acetivorans C2A. Heterologous expression of MaarsM was shown to confer As(III) resistance to an arsenic-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…strain 5508, Methanosarcina acetivorans C2A, and three cyanobacterial species have been functionally characterized previously (17,19,21,22). In the present study, we showed that P. alcaligenes was able to biotransform As(III) into methylated As species, with DMAs(V) being the predominant product.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…strain 5508, Methanosarcina acetivorans C2A, and three cyanobacterial species have been functionally characterized previously (17,19,21,22). In the present study, we showed that P. alcaligenes was able to biotransform As(III) into methylated As species, with DMAs(V) being the predominant product.…”
Section: Discussionsupporting
confidence: 57%
“…Of the arsenitemethylating bacteria, Rhodopseudomonas palustris (17), Streptomyces sp. strain GSRB54 (18) and Methanosarcina acetivorans C2A (19) have been studied in detail. The enzymes that catalyze As methylation, As(III) S-adenosylmethionine methyltransferases (ArsMs), have been purified and characterized from these bacteria.…”
mentioning
confidence: 99%
“…The huge difference between the sequences may explain the difference in methylation products. In addition, As(III) was seen to be transformed to DMA(V) within 30 min, and the catalytic rate of SpArsM was much faster than that of other ArsMs (Qin et al, 2009;Wang et al, 2014a;Zhang et al, 2015). Meanwhile, the intermediate MMA(III) and MMA(V) were absent in the in vitro enzyme activity assays when the reaction was performed at optimal conditions, and only MMA(V) was observed when the enzyme was impaired, for example under higher or lower temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study also differed from some previous anaerobic studies in that DMAs(V) and not MMAs(V) was the dominant methylated product. 23,24 An explanation for prior observations of greater methylation efficiency in aerobic relative to anaerobic cultures is that toxic trivalent methylated species are quickly oxidized to less toxic pentavalent derivatives in aerobic systems, 15 precluding the accumulation of the toxic form of As. The anaerobic culture examined in this study diverged significantly from the pattern of limited methylation by anaerobic cultures, however, demonstrating that robust arsenic methylation is possible in anaerobic systems.…”
Section: ■ Discussionmentioning
confidence: 99%